ANALISIS FEMINISME RADIKAL TOKOH FIRDAUS DALAM NOVEL PEREMPUAN DI TITIK NOL KARYA NAWAL EL SAADAWI - Maziah Maziah; Sumiharti Sumiharti; Erlina Zahar (Universitas Batanghari, 2018)
The purpose of this research is to describe the radical feniminism in the main character in the novel Perempuan Di Titik Nol by Nawal El-Saadawi which refers to three aspects, they are: (1) violence against woman, (2) woman’s exploitation, and (3) role of woman. This research is descriptive qualitative. The data is taken from the characters’ utterances and from the story which represents radical feminism aspects. The data are analyzed by using structural approach. Based on the result, it is found that radical feminism in the main character in the novel Perempuan Di Titik Nol karya Nawal el-Saadawi refers to these three aspects, they are: (1) 15 utterances refer to violence against woman, (2) 8 utterances refer to woman exploitation (3) 9 utterances refer to the role of woman, which is supported by the dialog or utterances in the novel.Key Words: radical feminism, character, novel Perempuan di Titik Nol